IDENTIFIKASI KEJADIAN KEKERASAN PADA ANAK DI KOTA MALANG - Thathit Manon Andini (Jurnal Perempuan dan Anak, 2019)
The aims of this research is to identify the Children abuse faced by the elementary students in Malang City. The research design used in this research is descriptive research. The  pupolation of this research were the students of elementary school in 3,4,5 and 6 grade, specifically in Muhammadiyah Elementary School in Malang City.By using random sampling with 347 students as sample, it was identified that there the students’ abuse covers physical abuse, verbal abuse, emotional abuse, and sexual abuse. Based on the  age, the students who received the abuse are around 8 years old (14%),  9 years old (23%), 10 years old(31%), 11 years old (21%), 12 years old (8%), and 13 (3%). The research was conducted on August 2017. The instruments used are the guided questionaire. It means thet the researchers still give the guidance to the children how to answer the question with the cosidering that they still lack of knowledge filling the questionaire.The result of the researh show that the form of abuse the respondents received are physical abuse, verbal abuse, emotional abuse and sexual abuse. It was found that the children who experienced the abuse in the range of 9 years olad (23%), 10 years old (31%), and 11 years old (21%). Based on the family conditioan, the children who often face the abuse is mostly the only children in the falily up to three brothers  and sisters (23-30%). The mother of the children who often receive the abuse is home wife without income, the compony workers or staf. Stressful condition force the mother do the abuse to their children. In the side of father profession,  the children who received the abuse, they belong to the father who works as a staf in a company, unemployment, illness, poorhouse condition, a large than average family size, the presence of a new baby, and disable.